Mekanisme GCG Terhadap Kinerja Keuangan dengan Kinerja Lingkungan sebagai Variabel Intervening - Juliasari, Deni; Ana, Selvia Roos; Sochib (RELASI : JURNAL EKONOMI, 2024)
This study integrates the variables that have been studied into a mediation analysis. The population used in this study are Manufacturing Companies Listed on the IDX and PROPER for the 2019-2021 period, totaling 69 companies. The selection or sampling method in this study used a purposive sampling technique, namely the selection or sampling technique with certain considerations and criteria in mind. So that the sample data in this study were 117. The analysis technique used was multivariate with Structural Equation Modeling Partial Least Sequare (SEM-PLS). The research results of the board of directors have an effect on financial performance but have no effect on environmental performance, the board of commissioners has an effect on environmental performance but has no effect on financial performance, an independent board of commissioners has an effect on environmental performance but has no effect on financial performance, the audit committee has no effect on financial performance and environmental performance, institutional ownership has no effect on financial performance and environmental performance, managerial ownership has no effect on financial performance on environmental performance. Environmental performance cannot be an intervening variable in the relationship between the proportions of the board of directors, board of commissioners, independent board of commissioners, audit committee, institutional ownership, and managerial ownership of financial performance.